Akanthomyces lepidopterorum, a new lecanicillium-like species - Chen, Wan-Hao; Han, Yan-Feng; Liang, Jian-Dong; Liang, Zong-Qi (Phytotaxa, 2020)
During a survey of entomopathogenetic fungi from Southwest China, a new species, Akanthomyces lepidopterorum was found on an undetermined lepidopteran larva. It differs from other species based on mostly smaller conidia, mononematous conidiophores and moderate length of phialide. Both the morphological identification and phylogenetic analysis of combined ITS, LSU and RPB2 sequence data support A. lepidopterorum as a new species. A new combination is also proposed in the genus Akanthomyces.